Kawasaki disease in a infant - Cotrina Malca, Diana (2018)
ABSTRACT Kawasaki disease is an acute febrile illness of childhood characterized by vasculitis of the middle-sized, extraparenchymal arteries with a predilection for the coronary arteries. The etiology remains obscure, which hinders efforts to develop a diagnostic test and targeted treatments. We present the case of a 9-month-old female patient admitted to the Edgardo Rebagliati Martins National Hospital due to fever, polymorphous rash on the thorax and lower limbs with central progression, associated with pruritus, conjunctival injection and edema of the hands and feet. Taking into account the physical examination and the results of the complementary studies carried out, Kawasaki disease was diagnosed, for which intravenous immunoglobulin (3 doses) and acetylsalicylic acid were indicated. Key words: Kawasaki disease; Pharmacotherapy; Vasculitis; Immunoglobulin. (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1599